2019
DOI: 10.3390/ijms20246299
|View full text |Cite
|
Sign up to set email alerts
|

O-GlcNAc Transferase Regulates Angiogenesis in Idiopathic Pulmonary Arterial Hypertension

Abstract: Idiopathic pulmonary arterial hypertension (IPAH) is considered a vasculopathy characterized by elevated pulmonary vascular resistance due to vasoconstriction and/or lung remodeling such as plexiform lesions, the hallmark of the PAH, as well as cell proliferation and vascular and angiogenic dysfunction. The serine/threonine hydroxyl-linked N-Acetylglucosamine (O-GlcNAc) transferase (OGT) has been shown to drive pulmonary arterial smooth muscle cell (PASMC) proliferation in IPAH. OGT is a cellular nutrient sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 82 publications
0
23
0
Order By: Relevance
“…It also affects the proliferation of smooth muscle cells. The vascular wall becomes thicker, and plexiform lesions are formed [ 107 ].…”
Section: Copdmentioning
confidence: 99%
“…It also affects the proliferation of smooth muscle cells. The vascular wall becomes thicker, and plexiform lesions are formed [ 107 ].…”
Section: Copdmentioning
confidence: 99%
“…The in vitro angiogenesis tube formation assay encompasses multiple features required for endothelial cells to form into vessel-like structures, including adhesion, migration, and tubule formation in a coordinated manner depending on the balance of pro-angiogenic and antiangiogenic factors [63]. This assay has been used to screen for inhibitors and to identify signaling mechanisms involved (for examples, see References [64][65][66]). We have focused mainly on VEGF and to a less extent on PEDF, as effectors of angiogenesis and angiogenesis inhibition, but a number of factors are involved to produce the end result of vessel formation.…”
Section: Discussionmentioning
confidence: 99%
“… 68 69 70 In rat aortic smooth muscle cells, plasminogen activator inhibitor-1 (PAI-1), a well-known stimulator of VSMC migration (especially in the setting of chronic transforming growth factor [TGF]-β1 activation), is upregulated via Sp1-binding to the PAI-1 promoter region through the release of a transcriptional repressor from Sp1 complexes under high-glucose conditions. 71 Barnes et al 72 demonstrated that higher O-GlcNAcylation of Sp1 in pulmonary arterial smooth muscle cells from idiopathic pulmonary arterial hypertension facilitated cell migration via increased expression of vascular endothelial growth factor. It was also shown that the increased expression of TGF-β1 in endothelial cells cultured under high-glucose conditions was mediated by elevated O-GlcNAcylation of Sp1, 73 which may be implicated in VSMC proliferation through the synthesis of proteoglycans and extracellular matrix proteins.…”
Section: Role Of O-glcnacylation In Diabetic Vasculopathymentioning
confidence: 99%